Four Strategies Of Murshid Tariqat In Optimizing Muzakiy Behavior In West Nusa Tenggara - Abdullah Abdullah; Akhmad Syahri; Muhammad Luthfi Abdullah (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2021)
Indonesia, with 87.18% Of Muslims, has a high zakat potential reaching 217 trillion per year. However, the law and various ways suggested by experts still fail in collecting zakat. Through the data of collecting zakat, which only reaches 1.2%, therefore, a new approach and way are needed to maximize the collection of zakat. Research with observations, documentation, and interviews found that murshid tariqat has a strategic role in maximizing zakat collection. Murshid had a strong influence on students. Students' adherence to murshid in religious and socio-political affairs reached an average of 98%. The readiness of students' obedience in terms of zakat reached 100%. The high compliance and willingness to comply is a reasonable step to maximize the murshid order's strategic role in collecting zakat. Murshid's strategic step in collecting zakat can be maximized through four stages; first, establishing institutions amil zakat infaq and sadaqah; second, socialization and education about the law and wisdom of zakat, third professionalism ammil, fourth, distribution of zakat transparent and on target